A PEIRCEAN SEMIOTIC ANALYSIS IN THE NETZWERK NEU A1 TEXTBOOK: CULTURAL REPRESENTATION OF THE “GUTEN APPETIT!" THEME - Regina Ameilia; Nurhafiza Yusro; Marisa Septiana Situmeang; Rira Wahyu Manullang; Dita Aulia Sihombing; Fitri Ervina Tarigan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Foreign language textbooks function not only as instructional media but also as cultural texts that construct specific representations of social life. This study investigates how cultural meanings are embedded in the Guten Appetit! theme of the Netzwerk Neu A1 textbook through the semiotic framework of Charles Sanders Peirce. Employing a qualitative descriptive method, the research analyzes visual illustrations and textual elements using Peirce’s triadic model of representamen, object, and interpretant, as well as his classification of hypoicons (image, metaphor, and diagram). The results indicated that visual and verbal signs in the Guten Appetit! theme of the Netzwerk Neu A1 textbook represented German dining culture through icons, indexes, and symbols. These signs reflected social values such as politeness, orderliness, and communal interaction, showing that the textbook not only taught language but also conveyed cultural meanings to beginner learners. The findings contributed theoretically by extending the application of Charles Sanders Peirce's semiotic theory to the analysis of cultural representation in foreign language textbooks. Practically, the study showed that visual and verbal signs in simple themes such as Guten Appetit! conveyed deeper cultural meanings and could support learners' intercultural understanding in German language learning.